IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK DI UNIVERSITAS ISLAM NEGERI SUNAN GUNUNG DJATI BANDUNG - Engkus Engkus; Nanang Suparman; Fadjar Trisakti; Mohammad Robby Rodhiya (Jurnal Governansi, 2019)
The implementation of public information disclosure in State Islamic University (UIN) Sunan Gunung Djati Bandung has not been optimal. At the time of initial observation, the researcher found some problems such as lack of UIN community participation and the public to request information, lack of some received informations, lack of supports from UIN officers and the government. The situation is also facilitated by lack of public information disclosure socialization conducted by UIN officers to UIN community and the public. The aim of the research is to describe the implementation of public information disclosure in UIN. The method of the research is a qualitative research. The informants of the research are 4 people who consist of the policy executives and the community who gets the impact of the policy. The data are collected from the field and library by interview, observation and documentation. The data are analyzed by Miles and Huberman’s analysis model including three lines of activity, namely data reduction, data presentation, and conclusion drawing. Viewed from aspects of sizes and standards of policy, resources, interorganizational communication and implementer activities, characteristics of implementer agents, implementer disposition/attitudes, and economic, social and political environments, the implementation of public information disclosure in UIN still finds many obstacles and lacks, so it has not been optimized. In order to be optimized, the research recommends to improve the public information disclosure socialization to UIN community and the public and the fulfillment of digital infrastructures in order to easily deliver information.Keywords: Policy Implementation, Public Information Disclosure, Public Policy.